Genital disorders, linear and testicular characteristics in Menz rams - Amare, H.; Toe, F.; Mukasa-Mugerwa, E.; Kassa, T.; Tibbo, Markos (Springer, 2001)
Clinical examination, bodily condition score (BCS), heart girth (HG), body length (BL), wither height (WH), and scrotal circumference (SC) were assessed on 486 mature Ethiopian Menz rams, on small farms, in local markets, and at the main abattoir in Addis Ababa from December 1994 to April 1995. Almost 27% of the rams were found to be unfit for breeding. Poor general condition, mainly in the form of respiratory disorders, was seen in 1.2% of the rams. Balanoposthitis, epididymitis and orchitis were the most common pathological conditions, affecting the external reproductive organs in 14.6%, 4.5% and 4.1% of the rams, respectively. Testicular calcification, cysts and testicular haemorrhagic lesions were detected in 4, 6 and 8, respectively, of the 60 rams examined at necropsy. The BCS, HG, BL and W H averaged 2.1 ± 0.5, 67.7 ± 5.0 cm, 60.1 ± 4.5 cm and 60.1 ± 4. 3 cm, respectively. The mean SC was 25.5 ± 3.9 cm and did not vary significantly with age (p > 0.05). Among the linear body measurements, the highest correlation was between BL and WH (r = 0.66). SC was found to be most closely correlated to HG (r = 0.46). More investigations into the relationship between the present findings and actual fertility, and on their practical application in the selection of rams for breeding is recommended.